2001
DOI: 10.1034/j.1399-0012.2001.150401.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of late acute rejection after cadaveric kidney transplantation

Abstract: AR had a deleterious impact on graft survival, particularly if occurring after 90 d. AR episodes should therefore be divided into early and late phases. In view of the very poor graft survival associated with LAR, it is important to gain further insight into the main aetiological factors. Those such as suboptimal CyA blood levels and non-compliance with medication should be further investigated with the aim of developing more effective immunosuppressive regimens in order to reduce the incidence of LAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 34 publications
1
53
2
Order By: Relevance
“…This finding could be related to the fact that AR occurred relatively late after transplantation (167 Ϯ 42 d). Indeed, previous reports have shown that late AR have a deleterious impact, especially when they occur after days 60 to 90 posttransplantation (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be related to the fact that AR occurred relatively late after transplantation (167 Ϯ 42 d). Indeed, previous reports have shown that late AR have a deleterious impact, especially when they occur after days 60 to 90 posttransplantation (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of chronic allograft nephropathy is not fully understood; however, acute rejection is an important risk factor. Especially late acute rejection episodes have been identified to have a strong correlation with late graft loss (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The 10-year graft SR for patients who have a previous episode of AR is 45%, reduced significantly compared to the patients with no AR (19). AR has a significant adverse impact on deceased donor allograft survival (18)(19)(20)(21), especially occurring after 3 months (20). Our patients have experienced less acute rejection episodes (21.8%), most likely because of their low immunologic risk.…”
Section: Discussionmentioning
confidence: 80%
“…Acute rejection is seen in 43.3-50.8% of DDKTx patients (18)(19)(20)(21). The 10-year graft SR for patients who have a previous episode of AR is 45%, reduced significantly compared to the patients with no AR (19).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation